Late Cenozoic Yushe Basin, Shanxi Province, China: Geology and Fossil Mammals Volume I:History, Geology, and Magnetostratigraphy - Tedford, Richard H.; Qiu, Zhan-Xiang.; Flynn, Lawrence J. (Vertebrate Paleobiology and Paleoanthropology, 2013)
The Late Cenozoic Yushe Basin, Shanxi Province, China embodies the bulk of our knowledge on successions of terrestrial vertebrates in the northern part of East Asia. Everything we know about Asian mammals of the last 6 million years has a historical basis in the documentation of the geology of Yushe. This volume introduces the basin in its geological setting, describes the succession of fossiliferous strata, and shows how it is dated. It develops an unsurpassed level of precision for its age control. Geological maps and stratigraphic sections provide the backbone for individual studies to follow on varied fossil groups. The volume explores the history of exploration of the last century in Yushe Basin and places development of paleontology there into the context of the birth of the modern epoch of science in China.